3 a 2 + 2 b 2 + c 2
Given that a , b and c are positive real numbers satisfying a + 2 b + 3 c = 2 1 , find the minimum value of the expression above.
Give your answer in 3 significant figures.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By Cauchy Schwarz Inequality ,
( ( 3 a ) 2 + ( 2 b ) 2 + ( c ) 2 ) ( ( 3 1 ) 2 + ( 2 ) 2 + ( 3 ) 2 ) ≥ ( a + 2 b + 3 c ) 2
⟹ Minimum value of our expression is 0 . 0 2 2 0 5 8 8 2 3 5 2 .
Problem Loading...
Note Loading...
Set Loading...
Similar solution to @Harsh Shrivastava , perhaps better presented.
By Cauchy-Schwarz inequality :
( 3 1 3 a + 2 2 b + 3 c ) 2 ( a + 2 b + 3 c ) 2 ( 2 1 ) 2 ⟹ 3 a 2 + 2 b 2 + c 2 ≤ ( ( 3 1 ) 2 + ( 2 ) 2 + ( 3 ) 2 ) ( ( 3 a ) 2 + ( 2 b ) 2 + ( c ) 2 ) ≤ ( 3 1 + 2 + 9 ) ( 3 a 2 + 2 b 2 + c 2 ) ≤ 3 3 4 ( 3 a 2 + 2 b 2 + c 2 ) ≥ 4 ( 3 4 ) 3 ≈ 0 . 0 2 2 0 6
By Lagrange multipliers :
The problem can also be solved using Lagrange multipliers.
Let F ( a , b , c , λ ) = 3 a 2 + 2 b 2 + c 2 − λ ( a + 2 b + 3 c − 2 1 ) , where λ is the Lagrange multiplier.
Then, we have: ∂ a ∂ F = 6 a − λ , ∂ b ∂ F = 4 b − 2 λ , ∂ c ∂ F = 2 c − 3 λ and ∂ λ ∂ F = a + 2 b + 3 c − 2 1 .
Equating ∂ a ∂ F = ∂ b ∂ F = ∂ c ∂ F = ∂ λ ∂ F = 0 . we have: 6 a = 2 a = 3 2 c = λ ⟹ b = 3 a and c = 9 a . Substituting in a + 2 b + 3 c = 2 1 , we have a = 6 8 1 , and substituting that in 3 a 2 + 2 b 2 + c 2 we get the minimum. ⟹ 3 a 2 + 2 b 2 + c 2 = ( 3 + 1 8 + 8 1 ) a 2 = 6 8 2 1 0 2 ≈ 0 . 0 2 2 0 6